Protocol for muscle fiber type and cross-sectional area analysis in cryosections of whole lower mouse hindlimbs - Edmund Battey; Matthieu Dos Santos; Dipsikha Biswas; Pascal Maire; Kei Sakamoto (STAR Protocols)
Summary: We outline a protocol to visualize all mouse lower hindlimb skeletal muscles simultaneously. We describe procedures for orientating the whole lower hindlimb in gum tragacanth prior to freezing, simplifying the proceeding experimental steps, and enhancing the comprehensiveness of characterizations. We then detail steps for quantifying muscle fiber size and fiber type characteristics in a single cryosection using histochemistry and immunofluorescence. This protocol can be applied to histological and (immuno)histochemical evaluations such as muscle regeneration, fibrosis, enzymatic activity, and glycogen content. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.